PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PROBING PROMPTING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF IPA FISIKA SISWA DI SMP NEGERI 7 TAMBANG KABUPATEN KAMPAR - Masraudhah, Masraudhah; Azizahwati, Azizahwati; Syahril, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aim of this research is to describe the improvement of cognitive learning outcomes of Physics IPA through the application of cooperative learning model Probing Prompting type. This research is Quasi Experimental Design with Nonequivalent Control Group Design. The sample of the study were the students of class VIII A as the experimental class and class VIII B as the control class. The data collection instrument was a test of cognitive learning outcomes given to the sample as pretest and posttest. Data analysis techniques used descriptive and inferential analysis. The results showed that the average ability of students with the application of cooperative learning model Probing Prompting type is higher conventional learning. It can be concluded that the application of cooperative learning model Probing Prompting type can improve students’ learning outcomes of Physics IPA in Force in SMP Negeri 7 Tambang Kampar.Keywords: Cooperative Learning, Probing Prompting Type, Cognitive Learning Outcomes